Preparation and in vivo characterization of 51MnCl2 as PET tracer of Ca2+ channel-mediated transport - Stephen A. Graves (Nature Portfolio, 2017)
Abstract Manganese has long been employed as a T1-shortening agent in magnetic resonance imaging (MRI) applications, but these techniques are limited by the biotoxicity of bulk-manganese. Positron emission tomography (PET) offers superior contrast sensitivity compared with MRI, and recent preclinical PET studies employing 52gMn (t1/2: 5.6 d, β+: 29%) show promise for a variety of applications including cell tracking, neural tract tracing, immunoPET, and functional β-cell mass quantification. The half-life and confounding gamma emissions of 52gMn are prohibitive to clinical translation, but the short-lived 51Mn (t1/2: 46 min, β+: 97%) represents a viable alternative. This work develops methods to produce 51Mn on low-energy medical cyclotrons, characterizes the in vivo behavior of 51MnCl2 in mice, and performs preliminary human dosimetry predictions. 51Mn was produced by proton irradiation of electrodeposited isotopically-enriched 54Fe targets. Radiochemically isolated 51MnCl2 was intravenously administered to ICR mice which were scanned by dynamic and static PET, followed by ex vivo gamma counting. Rapid blood clearance was observed with stable uptake in the pancreas, kidneys, liver, heart, and salivary gland. Dosimetry calculations predict that 370 MBq of 51Mn in an adult human male would yield an effective dose equivalent of approximately 13.5 mSv, roughly equivalent to a clinical [18F]-FDG procedure.